The house in the pines : a novel - Reyes, Ana, 1982- (New York : Dutton, an Imprint of Penguin Random House LLC, 2023)
Seven years after the mysterious death of her best friend, Aubrey, Maya comes across a recent YouTube video in which a young woman dies in front of the same man Aubrey did, leading her back to a New England cabin to finally uncover a truth that could save her.
Keywords: Murder -- Fiction; Best friends -- Fiction; Memory -- Fiction; Cold cases (Criminal investigation) -- Fiction; Massachusetts -- Fiction; Thrillers (Fiction)